Antecedents of Purchase Intention of Co-Branded Aerostreet Products: An Empirical Approach Towards Consumers in Surakarta - Kussudyarsana; Fitriasari, Defita (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to investigate the antecedents of purchase intention for Aerostreet co-branded products: an empirical approach targeting consumers in Surakarta. The study focuses on consumers who reside in Surakarta, are familiar with Aerostreet products, and are aged 17-30 years. A non-probability sampling technique was employed, with a sample size of 180 respondents. The research employs a quantitative approach, utilizing a structured questionnaire and observations as data collection methods. Data analysis was conducted using Structural Equation Modeling (SEM) with PLS 3.0. The results show that Product Fit has a significant effect on Brand Fit, Product Fit has a significant effect on co-branded Attitude, Brand Fit positively and significantly influences co-branded Attitude, and co-branded Attitude impacts Purchase Intention. Furthermore, co-branded Attitude mediates the relationship between both Product Fit and Purchase Intention, as well as Brand Fit and Purchase Intention.